A Framework to Evaluate the Benefit of Seismic Upgrading. Issue 2 (May 2018) - Galanis, Panagiotis; Sycheva, Anastasia; Mimra, Wanda; Stojadinović, Božidar
Earthquakes are among the most catastrophic natural disasters. Existing buildings constructed in earthquake prone locations prior to 1970s generally do not meet the criteria of modern seismic design codes. Structural seismic upgrading is a very effective strategy to mitigate the earthquake risk for existing structures. However, in many cases, seismic upgrade design is criticized as overly conservative resulting in expensive structural interventions. The present study proposes a framework that combines key elements of the performance-based seismic design with the actuarial "frequency-severity" method to perform a cost-benefit analysis of structural seismic upgrading. A curve that quantifies the avoided losses and casualties for different levels of partial seismic upgrade at the site of interest is introduced. This curve provides a tool that enables engineers to optimize rapidly, at a preliminary design level, the seismic upgrading strategy using a cost-benefit analysis. The proposed framework is applied to existing residential buildings located in two different seismic hazard environments, namely Zurich (Switzerland) and L'Aquila (Italy), to identify the optimal seismic upgrading level.